Homography-based visual servoing for underactuated VTOL UAVs tracking a 6-DOF moving ship - Huang, Yanting (2022)
This paper develops a novel homography-based visual servo control method for the vertical take-off and landing (VTOL) unmanned aerial vehicle (UAV) tracking the trajectory of a 6 degrees of freedom (6-DOF) moving ship. Different from the classical homography-based visual servoing which is only suitable for the trajectory tracking of a planar moving target, an extended homography-based visual servoing framework is proposed to track the trajectory of a 6-DOF moving target regardless of its time-varying rotational motion. Taking entries in the homography matrix as feedback, the visual dynamics of UAV is established and decoupled into a translational motion sub-dynamics and an attitude sub-dynamics based on the hierarchical control strategy. In the translational motion subsystem, the robust controller is designed by embedding the nonlinear differentiator, the adaptive method, and a smooth saturation model in the backstepping control scheme. The saturation model is introduced to generate the constrained control inputs to ensure the nonsingular attitude extraction and help the visual points remain in the camera's field of view (FoV) simultaneously. In the attitude subsystem, a robust state-constrained control method is proposed by utilizing a robust control barrier function (RCBF), the quadratic programming (QP) and a saturation model to guarantee the visibility, where RCBF can accommodate unknown dynamics. The theoretical analysis demonstrates the asymptotic stability of the closed-loop system. Simulations are carried out to further validate the controller performance.